Malaya and its history including a history of Malaya and early Indian influence in Malaysia (and other essays) - Winstedt, Richard 1878-1966; R J Wilkinson (Richard James) 1867-1941 (Silverfish Malaysian classics, 2020)
A political system, art, science and literature may be taken to be the essential attributes of civilisation and even in 1511 when the Portuguese took Malacca, the Malay had them all. A social sense, arising out of tribal solidarity, has always distinguished him from the Chinese, who giving up to the family what was meant for the state is a strong individualist. Accordingly, even before the Hindu period the Malay had a system of government by village gaffers and tribal chiefs, while during that period he learned to combine a respect for the divine right of kings with an ineradicable manly independence and to accept a compromise between absolute monarchy and rule by elders. Old Malacca had, in theory, a system of government by the divine king, advised by a cabinet of ministers, a prime minister and commander-in-chief, a minister for police and customs, a treasurer, a court chamberlain, an admiral and so on. As for art, the early Malay colonies on the peninsula were too small and Malacca too late to develop the fine Buddhist and Hindu art of their kinsmen in Palembang and Java, and what art they may have had time Islam and the Portuguese destroyed, leaving only patterns of fabrics copied from Indian models and some metal- work more chaste in design than most Indian pieces.